A neurobehavioral therapy approach to the rehabilitation and support of persons with brain injury: Practice-based evidence from a UK charitable rehabilitation provider - Coetzer, Rudi; Ramos, Sara da Silva (Frontiers in Rehabilitation Sciences, 2022)
Background: The treatment and rehabilitation for people with acquired brain injury is continually evolving, with increasing recognition of the importance of approaches that adopt a multi-disciplinary biopsychosocial perspective focused on improving adjustment, social participation, and wellbeing. However, there is significant variability as to how such approaches are delivered, across the various stages of recovery, rehabilitation settings, and within different healthcare systems. Objective: This paper describes the neurobehavioral therapy (NBT) approach to brain injury rehabilitation adopted in our charitable organisation. We also report how the NBT approach evolved and adapted in response to changes in referral patterns, and patient needs within a broader, longer-term clinical pathway. Methods: Analysis of standardised outcome data were completed to investigate the effectiveness of our approach. Case vignettes are provided to illustrate the key components of the approach. Results: We report data suggesting that the approach is effective in delivering positive outcomes for patients. Furthermore, the data show differences in presentation between three clinical streams (restoration, compensation, and scaffolding) within the NBT approach. Conclusions: This paper describes how we adapted and evolved the ‘traditional’ neurobehavioral approach to brain injury rehabilitation into a model of delivery that can benefit a more diverse range of people living with the heterogenous and long-term consequences of brain injury.